The Effect Of Covid-19 Pandemic And International Human Resource Management Practices On Multinational Corporation’s Performance: A Mediator Of It-based Challenges - Maharaja, Thripurasundere A/p K. (2023)
The outbreak of COVID-19 has significantly affected various aspects of society, including the economy, healthcare, job design, job security, and the global business environment, particularly impacting multinational companies (MNCs). This pandemic has triggered unprecedented changes in human resource departments and practices, leading MNCs to adapt and modify their International Human Resource Management (IHRM) strategies, such as training and development, staffing, and compensation policies. Furthermore, the increased reliance on Information Technology (IT) and challenges related to remote work and Electronic Human Resource Management (e-HRM) have been noteworthy aspects of this transformation. This thesis aims to investigate the direct and indirect relationships between the COVID-19 pandemic, IHRM practices, IT-based challenges, and the performance of MNCs operating in various sectors in Malaysia. A questionnaire survey was conducted, gathering data from 172 HR professionals working in MNCs. The Partial Least Squares–Structural Equation Modelling (PLS-SEM) technique was employed to analyze the collected data.The study's findings indicate that the COVID-19 pandemic has a direct impact on IHRM practices, including training and development, staffing, and compensation policies. However, there is no direct and significant relationship between the pandemic and MNCs' overall performance. Only staffing from IHRM practices has a significant, direct effect on MNCs' performance